2005
DOI: 10.1063/1.1925782
|View full text |Cite
|
Sign up to set email alerts
|

Charging and emission effects of multiwalled carbon nanotubes probed by electric force microscopy

Abstract: Electrostatic properties of single-separated multiwalled carbon nanotubes (MWCNTs) deposited on a dielectric layer have been investigated by charge injection and electric force microscopy (EFM) experiments. We found that upon local injection from the biased EFM tip, charges delocalize over the whole nanotube length (i.e., 1-10 μ m), consistent with a capacitive charging of the MWCNT-substrate capacitance. In addition, the insulating layer supporting the nanotubes is shown to act as a charge-sensitive plate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 18 publications
1
26
1
Order By: Relevance
“…[2] that oxide charges play a minor role in our experiments. The discrepancies between our results and those of Zdrojek et al could arise from different sample preparation methods [2,3], different nanotube, or oxide quality. Indeed, it was shown, for example, that hydrogen annealing (as used during our sample preparation by chemical vapor deposition [2]) leads to an important reduction of the oxide trap density [4].…”
Section: Paillet Poncharal and Zahab Replycontrasting
confidence: 99%
“…[2] that oxide charges play a minor role in our experiments. The discrepancies between our results and those of Zdrojek et al could arise from different sample preparation methods [2,3], different nanotube, or oxide quality. Indeed, it was shown, for example, that hydrogen annealing (as used during our sample preparation by chemical vapor deposition [2]) leads to an important reduction of the oxide trap density [4].…”
Section: Paillet Poncharal and Zahab Replycontrasting
confidence: 99%
“…EFM has been used mainly to probe electric characteristics of single-walled and multi-walled carbon nanotubes. [40][41][42] Figure 7 shows the topographic images (top) of MWCNT, oxidized-MWCNT and aminated-MWCNT and the corresponding phase images of the lift mode (bottom). The mean diameters are 58 nm, 70 nm and 48 nm for MWCNT, oxidized-MWCNT and aminated-MWCNT, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Confirming Maxwell's pioneering results (Maxwell, 1878), experiments have shown that the charge distribution along a CNT subjected to an electric field is generally non uniform along the length, with evident end enhancements (Zdrojek et al, 2005(Zdrojek et al, , 2006Wang et al, 2008). The available experimental tests concern micron-long CNTs.…”
Section: Introductionmentioning
confidence: 69%
“…More recently, Griffith and Li (1996) and Jackson (2000) computed semi-analytic expressions of the charge density distribution in qualitative agreement with Maxwell's solution. Experimental tests proving charge end enhancements were carried out by Zdrojek et al (2005Zdrojek et al ( , 2006 and Wang et al (2008). These authors investigated the electrostatic properties of single-separated MWCNTs and single-walled CNTs deposited on a dielectric layer by charge injection and electric force microscopy experiments.…”
Section: Charge End Enhancementsmentioning
confidence: 99%